Synthesis, Structure Elucidation and Study of Antimicrobial Activity of Stannic(IV) Derivatives - Rehman, Sadiq-ur; Sherzaman, Saira; Aziz Choudhary, Muhammad; Aslam Mirza, Muhammad; Ansar Yasin, Khawaja (Asian Journal of Chemistry, 2013)
Six new organotin(IV) compounds with general formulae R2Sn(OL)2 and R3SnOL where R = CH3, n-C4H9, C6H5, OL = 4-oxypiperidine were synthesized by the reaction of R2SnCl2 and R3SnCl with stoichiometric amount of 4-hydroxypiperidine in dry ethanol/methanol. These compounds have been characterized by using multinuclear (1H, 13C, 119Sn) NMR and FT-IR spectroscopy. The spectroscopic results revealed that all the diorganotin(IV) compounds possess trigonal-bipyramidal geometry in solution and a tetrahedral environment around the tin atom in non-coordinating solvents, has been proposed for the triorganotin(IV) compounds. All the synthesized compounds were tested in vitro against a number of microorganisms to assess their biocidal activity. The biological activity of these compounds against various strains of bacteria and fungi has revealed promising activity in comparison with Amphotericin B and miconazole as reference drugs. LD50 values of some of the tested compounds showed cytotoxicity.